The Effect of Cooperative Learning Team-Games-Tournament Model Toward Students’ Science Learning Outcome - Nur Rahmah (ETDC: Indonesian Journal of Research and Educational Review, 2023)
Students studying science must be able to think critically, creatively, and aggressively. Learning should be planned in an engaging manner to maintain student engagement and produce high-quality learning. Teachers are expected to become proficient in multiple learning models in addition to using repetitive techniques or strategies when delivering material in class. In actuality, traditional and classical models are frequently employed by educators in the teaching and learning process. In order to make learning more relevant, educators should improve this learning model. The cooperative learning model is chosen to achieve this goal. The cooperative learning model is designed to encourage group cooperation and interaction between students. This research aims to analyze the improvement in science learning outcomes through the implementation of The study was conducted to explore the effectiveness of the TGT (team games tournament) cooperative learning model in the middle school in South Sulawesi for science learning outcomes. The research subjects were 21 junior high school students in grade 8. The type of research is pre-experimental through the one-group pretest-posttest design. The results showed that students' science learning outcomes increased significantly compared to the pretest score (sig. 0.00<0.05).